Development of a bivalent protein-based vaccine candidate against invasive pneumococcal diseases based on novel pneumococcal surface protein A in combination with pneumococcal histidine triad protein D - Afshari, Elnaz; Ahangari Cohan, Reza; Shams Nosrati, Mohammad Sadegh; Mousavi, Seyed Fazlollah (Frontiers in Immunology, 2023)
Extended efforts are geared toward improving effective strategies for pneumococcal vaccination, focusing on evaluating the potential of multivalent protein-based vaccines and overcoming the limitations of pneumococcal polysaccharide-based vaccines. In this study, we investigated the protective potential of mice co-immunization with two pneumococcal PhtD and novel rPspA proteins against pneumococcal sepsis infection.The formulations of each antigen alone or in combination were administered intraperitoneally with alum adjuvant into BALB/c mice three times at 14-day intervals. The production of antigen-specific IgG and (IgG1 and IgG2a) subclasses, as well as IL-4 and IFN-γ cytokines, were analyzed. Two in vitro complement- and opsonophagocytic-mediated killing activities of raised antibodies on day 42 were also assessed. Finally, the protection against an intraperitoneal challenge with 106 CFU/mouse of multi-drug resistance of Streptococcus pneumoniea ATCC49619 was investigated. Our findings showed a significant increase in the anti-PhtD and anti-rPspA sera IgG levels in the immunized group with PhtD+rPspA formulation compared to each alone. Moreover, the results demonstrated the synergistic effect with a 6.7- and 1.3- fold increase in anti-PhtD and anti-rPspA IgG1, as well as a 5.59- and 1.08- fold increase in anti-PhtD and anti-rPspA IgG2a, respectively. Co-administration of rPspA+PhtD elicited a mixture of Th-2 and Th-1 immune responses, more towards Th-2. In addition, the highest complement-mediated killing activity was observed in the sera of the immunized group with PhtD+rPspA at 1/16 dilution, and the opsonophagocytic activity was increased from 74% to 86.3%. Finally, the survival rates showed that mice receiving the rPspA+PhtD formulation survived significantly longer (100%) than those receiving protein alone or PBS and exhibited the strongest clearance with a 2 log10 decrease of bacterial load in blood 24h after challenge compared to the control group. In conclusion, the rPspA+PhtD formulation can be considered a promising bivalent serotype-independent vaccine candidate for protection against invasive pneumococcal infection in the future.